2021
DOI: 10.3389/fpls.2021.739282
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Zinc Efficiency-Associated Loci in Maize

Abstract: Zinc (Zn) deficiency, a globally predominant micronutrient disorder in crops and humans, reduces crop yields and adversely impacts human health. Despite numerous studies on the physiological mechanisms underlying Zn deficiency tolerance, its genetic basis of molecular mechanism is still poorly understood. Thus, the Zn efficiency of 20 maize inbred lines was evaluated, and a quantitative trait locus (QTL) analysis was performed in the recombination inbred line population derived from the most Zn-efficient (Ye47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 115 publications
(140 reference statements)
2
5
0
Order By: Relevance
“…In addition, Zn concentration of the sensitive inbred line K22 was 2.2-fold and 1.4-fold higher than those of tolerant inbred lines BY815 and DAN340, respectively, indicating that Zn-efficient genotypes may not necessarily have higher shoot Zn concentrations when compared with Zn-inefficient genotypes. Furthermore, our previous results confirmed that Zn efficiencies based on shoot and root dry weights were not correlated with Zn concentrations in the shoot and root of twenty maize inbred lines which contained K22, BY815, and DAN340 [25]. Zn deficiency significantly enhanced shoot concentrations of iron (Fe) and manganese (Mn) for K22 by 96.2% and 34.9%, respectively, whereas it had no effects on Fe and Mn concentrations of BY815 and DAN340 (Figure 2c,d).…”
Section: Phenotypic Variation In Zn Deficiency Tolerancesupporting
confidence: 70%
See 4 more Smart Citations
“…In addition, Zn concentration of the sensitive inbred line K22 was 2.2-fold and 1.4-fold higher than those of tolerant inbred lines BY815 and DAN340, respectively, indicating that Zn-efficient genotypes may not necessarily have higher shoot Zn concentrations when compared with Zn-inefficient genotypes. Furthermore, our previous results confirmed that Zn efficiencies based on shoot and root dry weights were not correlated with Zn concentrations in the shoot and root of twenty maize inbred lines which contained K22, BY815, and DAN340 [25]. Zn deficiency significantly enhanced shoot concentrations of iron (Fe) and manganese (Mn) for K22 by 96.2% and 34.9%, respectively, whereas it had no effects on Fe and Mn concentrations of BY815 and DAN340 (Figure 2c,d).…”
Section: Phenotypic Variation In Zn Deficiency Tolerancesupporting
confidence: 70%
“…Evidence for identifying candidate genes by the QTLs colocalized by the loci detected in different populations have been recorded by multiple studies in maize [14,39,40]. Apart from the QTLs detected in the KB and DK populations in this study, we also used the QTLs identified in the Ye478×Wu312 (YW) RIL population to further determine the QTL colocalization among different populations [25]. Five QTL colocalization intervals were identified in eleven QTLs detected by different traits in the KB, DK, and YW RIL populations: two localizations on chromosome 1 and three localizations on chromosome 2 (Figure 7, Table 3).…”
Section: Qtl Colocalization and Candidate Genes Identificationmentioning
confidence: 99%
See 3 more Smart Citations